Influence of ESG Performance on Shaping the Environmental Kuznets Curve: Evidence from the Expanded Persian Gulf Region - Abdelkefi, Ines; Smaoui, Aida; Ezzine, Hanene (International Journal of Energy Economics and Policy, 2026)
This study investigates the dynamic interplay between economic growth, Environmental, Social, and Governance (ESG) performance, and environmental degradation in the expanded Persian Gulf region. Using a panel ARDL-PMG approach on data from 2018 to 2023 across eight countries, we confirm an inverted U-shaped Environmental Kuznets Curve (EKC), showing that economic growth initially increases CO₂ emissions but eventually leads to reductions beyond a certain income threshold. ESG performance significantly mitigates emissions and moderates the GDP-CO₂ relationship through the interaction term, lowering the EKC turning point and accelerating the stage at which economic growth leads to environmental improvements. The error correction term indicates rapid adjustment toward long-run equilibrium, highlighting the responsiveness of the system to economic and policy changes. These findings emphasize the importance of integrating ESG considerations into national policies, promoting sustainable corporate practices, and supporting green investments to achieve low-carbon and sustainable growth. This study advances the literature by embedding ESG performance within the Environmental Kuznets Curve framework, capturing its moderating role on economic growth,and enabling a more precise estimation of its influence on the EKC turning point. These insights provide both a theoretical contribution and guidance for policymakers, pointing them toward strategies that embed ESG principles, foster green investments, strengthen governance transparency, and accelerate the transition to low-carbon and sustainable growth in strategically important economies.